Outdoor Learning Model for Islamic Religious Education in the Independent Learning Curriculum - Koiy Sahbuddin Harahap; Sawaluddin Sawaluddin (Khazanah Pendidikan Islam, 2025)
The aim of this research is to determine the Outdoor Learning Model for Islamic Religious Education in the Independent Learning Curriculum. This type of research is field research. The research was conducted at STAI Rokan. The number of respondents in this study was 3 people from lecturers, leaders and 25 students. The data collection techniques used in this research are, Observation, Interviews, and Documentation. Data analysis techniques are efforts made by l) data reduction, 2) data presentation and 3)  conclusion drawing/verification. Implementation of the outdoor learning model Religious education Islam, has several stages, namely the lecturer provides an explanation, carry out practices according to the provisions, and evaluate. Learning outside the classroom feels exciting. Students become more active in learning, asking each other questions and answers. Students become more confident, accustomed to discussing and expressing opinions. It also makes learning more communicative. Meanwhile, the disadvantage of outdoor learning is that there are students who are busy playing, chatting and joking with their friends rather than discussing the material. Students lack focus in studying. Students become more difficult to manage when studying outside the classroom than studying in the classroom. Here is the relevance of outdoor learning to Islamic religious education; Spiritual Aspect,  Moral and Ethical Aspects, Knowledge Aspect and  Skill Aspect